Flow analysis of injection molds - Kennedy, Peter (Hanser Publishers, 2013)
Injection molding is arguably the most successful area of modeling and simulation for any polymer forming process. This is demonstrated by the number of companies devoted to development of software for molding simulation. Despite this, there are no texts aimed at users of such software and those who wish to improve the performance of existing software. This book is intended as a description of modern molding simulation technology for users and researchers. The book tries to be self contained and provides the major technologies used and assumptions made by commercial codes so as to provide a guide to users of limitations and a basis for further development. In the latter part of the book some ideas and approaches for improving simulation technology are provided. These are specifically aimed at fiber filled and semi-crystalline materials.
Keywords: Injection molding of plastics.; Viscous flow.; elektronické knihy; electronic books